1990
DOI: 10.1111/j.1464-410x.1990.tb14830.x
|View full text |Cite
|
Sign up to set email alerts
|

Midnight Removal: an Improved Approach to Removal of Catheters

Abstract: There is no recognised policy regarding the timing of urethral catheter removal, although early morning removal is commonly practised. Removing the catheter at midnight allows patients to return to a normal voiding pattern more rapidly and to leave hospital earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 0 publications
0
47
1
Order By: Relevance
“…A busier early-morning shift may consequently lead to delays in the actual ROC, and it has been suggested that the midnight ROC may be more amenable [2] . We are able to confi rm that there was no recatheterization at an unsociable hour when the catheter was removed late at night [2,5] ; however, this was necessary with 2 patients who had a ROC performed at 06.00 h.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A busier early-morning shift may consequently lead to delays in the actual ROC, and it has been suggested that the midnight ROC may be more amenable [2] . We are able to confi rm that there was no recatheterization at an unsociable hour when the catheter was removed late at night [2,5] ; however, this was necessary with 2 patients who had a ROC performed at 06.00 h.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors must be taken into account in deciding the time of ROC: patients' perspective, the resumption of the normal voiding patterns, and the likelihood of success of the ROC. Some authors [3] have shown no signifi cant difference between ROC at midnight and ROC at 06.00 h with regard to time to fi rst void and initial void volume, while others [2] have shown a longer time to fi rst void and a larger initial void volume with midnight ROC. An earlier discharge from hospital was noted with midnight ROC [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations